Tectonic Controls on Gas Hydrate Distribution Off SW Taiwan. Issue 2 (8th February 2019) - Berndt, C.; Chi, W.‐C.; Jegen, M.; Lebas, E.; Crutchley, G.; Muff, S.; Hölz, S.; Sommer, M.; Lin, S.; Liu, C.‐S.; Lin, A. T.; Klaeschen, D.; et al.
Abstract: The northern part of the South China Sea is characterized by widespread occurrence of bottom simulating reflectors indicating the presence of marine gas hydrate. Because the area covers both a tectonically inactive passive margin and the termination of a subduction zone, the influence of tectonism on the dynamics of gas hydrate systems can be studied in this region. Geophysical data show that there are multiple thrust faults on the active margin while much fewer and smaller faults exist in the passive margin. This tectonic difference matches with a difference in the geophysical characteristics of the gas hydrate systems. High hydrate saturation derived from ocean bottom seismometer data and controlled source electromagnetic data and conspicuous high‐amplitude reflections in P‐Cable 3‐D seismic data above the bottom simulating reflector are found in the anticlinal ridges of the active margin. In contrast, all geophysical evidence for the passive margin points to normal to low hydrate saturations. Geochemical analyses of gas samples collected at seep sites on the active margin show methane with heavy δ 13 C isotope composition, while gas collected at the passive margin shows light carbon isotope composition. Thus, we interpret the passive margin as a typical gas hydrate province fueled by biogenic production of methane and the active margin gas hydrate system as a system that is fueled not only by biogenic gas production but also by additional advection of thermogenic methane from the subduction system. Plain Language Summary: Gas hydrates are ice‐like crystals in marine sediments. They store an enormous amount of carbon and may be used as a future energy source. So far, little is known about the geological processes that control the distribution of gas hydrates. In this study we have combined a very wide range of geophysical and geochemical data to find out if the movements in the Earth crusts matter for the amount of gas hydrate in the surface rocks. We found out that there is much more hydrate in areas where there is a lot of movement than in those that are stable. This contradicts the previously held believes. It seems a good idea to focus hydrate exploration close to subduction zones rather than on old continental margins. Key Points: Gas hydrate formation depends on tectonically controlled advection of gas Offshore SW Taiwan gas hydrate saturations are higher in the active margin than in the passive margin Data evaluation combines seismic and controlled source electromagnetic data